Learners with Low Working Memory Capacity Benefit More from the Presence of an Instructor’s Face in Video Lectures - Yuyang Zhang; Jing Yang; Zhisheng (Edward) Wen (Journal of Intelligence, 2022)
This current study explores the influence of learners’ working memory capacity (WMC) on the facilitation effect of an instructor’s presence during video lectures. Sixty-four undergraduates were classified into high and low WMC groups based on their performance in an operation span task. They watched three types of video lectures on unfamiliar topics in a random order: video lectures with an instructor’s voiceover but without presence (VN), video lectures with the instructor’s face picture (VP), and video lectures with the same instructor talking (VV). We collected their eye movement data during the video lectures and their learning performance in the comprehension tests following each video. Two-way ANOVA and post-hoc analyses showed that the instructor’s presence significantly improved comprehension performance in only the low WMC group. They allocated more attention to the instructor’s face picture and talking head than the high WMC group. Our results highlight the value of the instructor’s presence as a social cue in video lectures, which is particularly beneficial for learners with a low WMC.